The Role Of Supportive Care To Overcome Depression and Improve Quality Of Life In Patients With Lung Cancer In Pulmonary Hospital - Wahyudi, Udi; Salmid, Amid; Subandi, Subandi; Hufad, Achmad; R. Hasanah, Viena; Handayani, Dini (Green Publisher Indonesia, 2022)
Supportive care is an interprofessional collaborative care approach between health personnel, modified through affirmative therapy, psychotherapy, and zoning, to optimize health services for information needs, emotional, spiritual, social or physical during diagnostic treatment or follow-up phase for patients with lung cancer. However, so far, hospital health personnel rarely use supportive care methods. Therefore, the aim of this study was to analyze the impact of implementing supportive care on depression and quality of life in lung cancer patients. The method used is a quasi-experimental design or pre-experimental design with a post-test approach of control group design. The sample size employed in this study was 44 respondents. The results showed that supportive care had a significant effect on depression and quality of life of lung cancer inpatients. A further recommendation from this study is that hospitals are expected to apply supportive care methods and carry out further research to develop innovative models of supportive care